Investigation to Predict Primary Implant Stability Using Frictional Resistance Torque of Tap Drilling - Kaien Wakamatsu; Kazuya Doi; Reiko Kobatake; Yusuke Makihara; Yoshifumi Oki; Kazuhiro Tsuga (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this experimental study was to investigate the correlation between the frictional resistance torque of tap drilling prior to implant placement and the primary stability after implant placement.